1993
DOI: 10.1002/gps.930080713
|View full text |Cite
|
Sign up to set email alerts
|

Deliberate self‐harm in the elderly: A survey of one London Borough

Abstract: SUMMARYThis article details the results of a retrospective case note study on deliberate self-harm in the elderly in the London Borough of Tower Hamlets. There were 56 females and 32 males included in the study. The ages of the patients ranged from 65 to 90. Fifty-seven per cent of the sample had a depressive illness, most commonly found in the younger females and the older males. Over 50% of the sample had evidence of multiple health problems, particularly heart disease and arthritis. Over 900/0 of cases used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
77
2
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(95 citation statements)
references
References 17 publications
15
77
2
1
Order By: Relevance
“…These findings contrast with rates for suicide in old age, where the male to female ratio is around 4-6 : 1 (McIntosh, 1992). The majority of attempters were not married (Pierce, 1987;Upadhyaya et al, 1989;Merrill and Owens, 1990;Frierson, 1991;Nieto et al, 1992;Lyness et al, 1992;Nowers, 1993;Draper, 1994b;Schmid et al, 1994), with at least 45% of those aged 65 years and over being widowed. The divorcedlseparated account for 4-13% of attempts and have been reported to have the highest population rates (Hawton and Fagg, 1990).…”
Section: Demographycontrasting
confidence: 53%
See 2 more Smart Citations
“…These findings contrast with rates for suicide in old age, where the male to female ratio is around 4-6 : 1 (McIntosh, 1992). The majority of attempters were not married (Pierce, 1987;Upadhyaya et al, 1989;Merrill and Owens, 1990;Frierson, 1991;Nieto et al, 1992;Lyness et al, 1992;Nowers, 1993;Draper, 1994b;Schmid et al, 1994), with at least 45% of those aged 65 years and over being widowed. The divorcedlseparated account for 4-13% of attempts and have been reported to have the highest population rates (Hawton and Fagg, 1990).…”
Section: Demographycontrasting
confidence: 53%
“…Overall, drug overdose was consistently the most frequent method chosen, with up to a further 6% taking an overdose in combination with self-injury. Prescription drugs were most often used, mainly benzodiazepines (37-79% of overdoses), followed by analgesics (1 1-30%) and antidepressants (1 1-32%) (Hawton and Fagg, 1990;Merrill and Owens, 1990;Lyness et al, 1992;Nowers, 1993;Rifai et al, 1993;Draper, 1994b). This contrasts with the earlier studies, where barbiturates were the predominant drugs used (Batchelor and Napier, 1953;Burston, 1969).…”
Section: Methods Of Attempted Suicidementioning
confidence: 99%
See 1 more Smart Citation
“…205 Suicidal attempts in the elderly are often characterized by a greater degree of lethal intent. 208,211 Although it is often suggested that suicide in the elderly primarily is a question of undiagnosed, untreated depression, it was reported that two-thirds of elderly people who died by suicide in Gothenburg, Sweden, had a history of treatment for affective illness and 48% had had such treatment 6 months before their suicide. 212 These findings emphasize that once diagnosed, depression in the elderly must be managed with persistence.…”
Section: Consequences Of Mental Disordersmentioning
confidence: 99%
“…In the same population, sampling those with mental illness, 29% felt that life was not worth living, 9% had thought about taking their own life and 2% had seriously considered suicide. The relationship between suicidal ideation, deliberate self-harm and subsequent suicide is a complex one, but there is no doubt that the elderly are over-represented both in the statistics of suicide committed after deliberate self-harm and in the suicide statistics more generally (Nowers, 1993(Nowers, ,1997Hepple & Quinton, 1997).…”
Section: Suicidal Ideation In the Elderlymentioning
confidence: 99%